Simbol Agama Dan Budaya Dalam Iklan Politik Pilkada Analisis Semiotika Roland Barthes - Syafi’i, Muhammad (UIN Sunan Kalijaga Yogyakarta, 2019)
This study seeks to reveal the use of religious symbols (Islam) and reveal the meaning of the use of these symbols in the context of society in the regional elections (2015) in Banjarmasin. Therefore, the author uses Roland Barthes's semiotic theory to reveal the ideological meaning of symbols in relation to certain people's culture or habits. This research proves that the meaning of religious symbols appears as an effort to represent the piety of the candidates. Thus, these ideological symbols also exploit knowledge and regional history and religiosity.